PEMBERDAYAAN MASYARAKAT MELALUI KEGIATAN POSYANDU DAN EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) - Panca Radono; Titis Tika Anggraini; Asdayani Emba Pudang; Yubliter Mone; Gladys Bunga Cantika (LPPM Universitas Abdurrab, 2026)
The main tactic to improve health levels is empowerment-based community health development, particularly in terms of maximizing Integrated Health Posts (Posyandu) and practicing Clean and Healthy Living Behavior (PHBS). Problems faced by the people of Ngasem Village, Ngasem District, Kediri Regency include low knowledge and awareness of implementing PHBS, as well as the suboptimal use of Posyandu as a means of health education. The objective of this community service project is to enhance the role of Posyandu as a center for community-based health services and education, while also improving the community's understanding, attitudes, and practices regarding PHBS (Clean and Healthy Living Behavior). The implementation method uses a participatory approach through the stages of preparation, planning, implementation, evaluation, and follow-up. Activities include basic health services, interactive counseling, demonstrations of PHBS practices, and mentoring Posyandu cadres. The assessment uses pre-intervention tests, post-intervention tests, and direct observation of behavioral changes in the community. The results showed a significant increase in community knowledge about PHBS from 55% to 85%, proper handwashing practices from 50% to 80%, and increased community participation in Posyandu activities from 65% to 90%. Furthermore, Posyandu cadres experienced increased capacity to provide health education independently. It was concluded that this training was successful in increasing community knowledge and adherence to clean and healthy living practices. Recommendations are given for the need for program sustainability through strengthening the role of cadres, cross-sector support, and the implementation of routine and ongoing health education to achieve an independent and healthy community.